Edukasi dan Simulasi Penanganan Luka Bakar di Lingkungan Sekolah - Santi Herlina; Vionita Apriliana; Bonieta Dwi Lestari; Widya Astuti; Indri Zalwa; Farikhah Farikhah; Nur Alfidah Rezafar (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Burns can occur anywhere, including at school, with students’ activities such as the use of laboratory equipment that may contain flammable fluids, contact with electrical terminals, and touched by the burning vehicle muffler. Based on interviews with several people at SMA Negeri 6 Depok related to health education and simulation of burn treatment, the results were obtained that school residents had never received any education related to burns. The purpose of this community service is to improve students’ knowledge, action, and practices for burn first aid. The target audience for this activity is 30 committees of Red Cross Youth from SMA Negeri 6 Depok which was held in October 2022. Methods used in this community service are health education by audiovisual, demonstration, and interactive simulations. The materials for health education include burn types, burn first aid, burn treatment, prevention of burn infections, burn complications, and demonstration of the use of fire extinguisher. The result of this activity showed a good impact on participants, which was an increase of knowledge that was proven by the result of the average pretest score being 83, then after the health education and demonstration, the average post test score increased to 96,3. The knowledge gained by Red Cross Youth students can be further improved and developed so that it can motivate the school community to realize the emergency and importance of burn problems.